THE ORIGIN AND SIGNIFICANCE OF THE ANCIENT TRADITION OF DRINKING KOUMISS “ULUSH” AMONG THE ALAI KYRGYZ “MEN’S UNIONS” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The Kyrgyz have many customs and rituals that reflect life in the primitive communal system and socio-economic relations in it. These traditions include family relations of the Kyrgyz, coming to the aid of relatives in good and bad times, ways of eating, family strength, relationships within the tribe (clan) (older and younger), waiting for a godson, etc. can be an example. The preservation of social relations in the primitive communal system undoubtedly confirms the antiquity of the people, the belonging of its culture to the ancient era. One of the ancient traditions mentioned is the Kyrgyz “ulush”. This Kyrgyz tradition has existed since the early communal era and over time has significantly changed its form and meaning (has undergone a transformation); In its original meaning, it can be considered parallel to the “male unions”, which have spread to other peoples. Kyrgyz “joro olturush”, “bozo joro”, “sherine”, etc. It is important to know that traditions have the same meaning as primitive “male unions”
Keywords: Alai Kyrgyz, ulush, kuda-sook, tribe, tradition, koumiss, bozo, biy, kasakur.